DETERMINAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL - Nuriman Buchori Hasmi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2020)
This study aimed to analyze and prove the influence of competence and career development on work motivation and its implication toward employee’s performance of education and culture affairs offices at Banten province, both partially and simultaneously. The method used in this research were descriptive, survey and explanatory method with population size of 1.406 and sample size of 210 respondents. The method used to analysis data was SEM (Structural Equation Modeling). The research result, obtained the findings that competence, motivation and career development simultaneously had significant effect toward performance. Viewed as partial, Competence had dominantly toward employee’s performance. Concerning on direct and indirect effect that work motivation was being partial mediating. The study recommends that in order to improve employee’s performance which reflected by the dimension aspects of the quantity increased work motivation which reflected by the dimension needs to be affiliated and supported by increased competence reflected by the dimension of the ability and do repairs on a career development system reflected the dimension of chance of education and training